Clofazimine for Treatment of Cryptosporidiosis in Human Immunodeficiency Virus Infected Adults: An Experimental Medicine, Randomized, Double-blind, Placebo-controlled Phase 2a Trial. (11th April 2020) - Iroh Tam, Py; Arnold, S L M; Barrett, L K; Chen, C R; Conrad, T M; Douglas, E; Gordon, M A; Hebert, D; Henrion, M; Hermann, D; Hollingsworth, B; Houpt, E; et al.
Abstract: Background: We evaluated the efficacy, pharmacokinetics (PK), and safety of clofazimine (CFZ) in patients living with human immunodeficiency virus (HIV) with cryptosporidiosis. Methods: We performed a randomized, double-blind, placebo-controlled study. Primary outcomes in part A were reduction in Cryptosporidium shedding, safety, and PK. Primary analysis was according to protocol (ATP). Part B of the study compared CFZ PK in matched individuals living with HIV without cryptosporidiosis. Results: Twenty part A and 10 part B participants completed the study ATP. Almost all part A participants had high viral loads and low CD4 counts, consistent with failure of antiretroviral (ARV) therapy. At study entry, the part A CFZ group had higher Cryptosporidium shedding, total stool weight, and more diarrheal episodes compared with the placebo group. Over the inpatient period, compared with those who received placebo, the CFZ group Cryptosporidium shedding increased by 2.17 log2 Cryptosporidium per gram stool (95% upper confidence limit, 3.82), total stool weight decreased by 45.3 g (P = .37), and number of diarrheal episodes increased by 2.32 (P = .87). The most frequent solicited adverse effects were diarrhea, abdominal pain, and malaise. One placebo and 3 CFZ participants died during the study. Plasma levels of CFZ in participants with cryptosporidiosis were 2-fold lower than in part B controls. Conclusions: Our findings do not support the efficacy of CFZ for the treatment of cryptosporidiosis in a severely immunocompromised HIV population. However, this trial demonstrates a pathway to assess the therapeutic potential of drugs for cryptosporidiosis treatment. Screening persons living with HIV for diarrhea, and especially Cryptosporidium infection, may identify those failing ARV therapy. Clinical Trials Registration: NCT03341767. Abstract : We evaluated clofazimine for treatment of adults living with human immunodeficiency virus and cryptosporidiosis. Clofazimine was well tolerated but did not reduce Cryptosporidium excretion or diarrhea compared with adults treated with placebo. This trial forms a blueprint for future cryptosporidiosis therapeutic trials.